Molecular Structure of 4-Benzoyl-3-Ethylcarboxylate 1-(4-Methoxyphenyl)-5-Phenyl-1H-Pyrazole: A Combined Experimental and Theoretical Study - İnkaya, E.; Diner, M.; Korkusuz, E.; Yildirim, I. (Elsevier, 2012)
The title molecule, 4-benzoyl-3-ethylcarboxylate 1-(4-methoxyphenyl)-5- phenyl-1H-pyrazole, (C 26H 22N 2O 4), was synthesized and characterized by IR-NMR spectroscopy and single-crystal X-ray diffraction. In addition to the molecular geometry from X-ray experiment, the molecular geometry, vibrational frequencies and gauge-independent atomic orbital (GIAO) 1H and 13C NMR chemical shift values of the title compound in the ground state have been calculated using the spin-restricted Hartree-Fock (HF) and density functional theory (DFT/B3LYP) method with the 6-31G (d, p) basis set, and compared with the experimental data. To determine conformational flexibility, molecular energy profile of the tittle compound was obtained by semi-empirical (AM1) with respect to selected degree of torsional freedom, which was varied from -180° to +180°in steps 10°. Besides, molecular electrostatic potential (MEP) distribution, frontier molecular orbitals (FMOs) and thermodynamic properties of the title molecule were investigated by theoretical calculations at the B3LYP/6-31G (d, p) level. © 2012 Elsevier B.V. All rights reserved.
Keywords: AM1 Semi-Empirical Method; DFT/HF Calculations; IR and NMR Spectroscopy; Molecular Electrostatic Potential (MEP); X-Ray Structure Determination